Systematic list of the fishes from Cerralvo Island, Baja California Sur, Mexico - F Galván-Magaña; LA Abitia-Cárdenas; J Rodríguez-Romero; H Pérez-España; H Chávez-Ramos (Ciencias Marinas, 1996)
The first check-list of fishes from Cerralvo Island, Baja California Sur, Mexico, is reported here. A total of 174 species, belonging to 132 genera and 70 families were registered. This list includes species collected and observed in the area between 1990 and 1993, as well as species previously reported in the literature between 1944 and 1993. Cerralvo Island has 77 species from the Panamic Province, 52 with a wide distribution in the eastern Pacific, 14 from the Mexican Province, 12 from the California Province, 5 species endemic of the Gulf of California and 14 species with Indo-Paciflc aftinity, including Gymnomuraena zebra, Heteropriacanthus cruentatus, Thalasoma grammaticum, Acanthurus triostegus, Scarus ghobban, Scarus rubroviolaceus, Zanclus cornutus, Arothron meleagris, Lutjanus viridis, Ostracion meleagris and Chaetodon falcifer.